Promoting Adult Student Success at Four-year Higher Education Institutions - Heidi A. Watson-Held (Adult Education Research Conference, 2015)
This study surveyed four-year institutions to examine the extent to which different categories of four-year institutions are meeting adult students’ needs and thereby promoting their success.
Keywords: adult friendly; motivators; barriers; access; persistence; success